Efeito do óleo essencial de Lavandula angustifolia sobre sintomas da esquizofrenia e extrapiramidais em camundongos - Cunha, Meiryland Melo da (2015)
Recommended as Complementary Medicine by World Health Organization (WHO), Aromatherapy is widespread around the world and uses 100% pure essential oils to prevent and/or treat health problems. Thus, these oils extracted from plants can be considered innovative tools for the treatment of certain pathologies, including mental disorders, because there is evidence for theirs effectiveness in treating disorders related to the Central Nervous System (CNS), and also has low toxicity and easy access. The most common mental conditions treated include mood disorders, anxiety, age-related cognitive decline, psychotic disorders, stress symptoms and chronic pain. This study aimed to investigate possible antipsychotic effects of essential oils but also verify whether it is able to relieve extrapyramidal symptoms. Males Swiss mice, albinos, weighing 32-49 grams, with approximately 2 months of age were used as experimental subjects. The essential oil Lavandula angustifólia was used through inhalation route (5 minutes). Data were analyzed using Graph Pad Prism, using the one-way ANOVA and the Kruskal-Wallis tests. In all comparisons, p<0.005 was considered statistically significant. In the hypolocomotion test with lavender oil treatment at concentrations of 2.5%; 5% and 10% we observed that ambulatory movement, rearing, number of jumps, rest (sc), distance (cm), velocity (mm/s), clockwise and counter-clockwise rotation the results showed that, in all parameters, there was a potentiation of the hipolocomotor effect of haloperidol. In the catatonia test induced by haloperidol (1 mg/kg intraperitoneal injection) treatment with the essential oil showed significant result (p<0.05) compared with animals pretreated with Haloperidol+Saline (GC-), being able to reduce time of catatonia. In the catatonia test induced by haloperidol via oral administration,also presented effect of statistical significance, it is possible to observe a decrease in catatonia time (s) of the oil group compared to Haloperidol+Saline (GC-) group. In the hyperlocomotion test induced by amphetamine (3 mg/kg intraperitoneal injection), the same parameters of hypolocomotion were observed, however, no statistically significant results were found when we compared the group treated with lavender and the Amphetamine+Saline (GC-) group in most tests. In the stereotypy test induced by apomorphine (20 mg/kg intraperitoneal injection), the treatment with the oil inhibited the stereotyped behavior with p <0.05. In Climbing test induced by apomorphine (same dose and route of administration) the animals treated with lavender decreased the climb behavior level when compared to animals treated with Haloperidol+Saline (GC-). After analyzing the results we can conclude that the essential oil of lavender, administered by inhalation route, can have a similar profile to antipsychotics because both alter neurotransmission involved in schizophrenia.